Person-Organization Fit and Turnover Intentions: Organizational Trust as a Moderator - Ramos,Juliana Rodrigues (2021)
Abstract This study examined the relationship between person-organization fit and turnover intentions, along with the moderating effect of organizational trust. The sample consisted of 381 workers of both genders (61% female) and average age of 39.23, who answered the on-line versions of organizational values, organizational trust and turnover intention measures. The results showed that the higher the person-organization fit related to conservatism and harmony values, the lower the turnover intention. Trust in the organization’s ethical standards moderated the relationship between person-organization fit related to dominance and autonomy values and turnover intention. It was concluded that a reduced trust in the organization’s ethical standards contributes to accentuate the negative relation between person-organization fit associated with such values and turnover intention.